Niveau D’etudes, Style Educatif Des Parents Et Resilience Scolaire Chez Des Enfants Deficients Auditifs De L’ecole Ivoirienne Pour Les Sourds (ECIS) - Mélissa, Kouassi Affoué (European Scientific Journal, ESJ, 2016)
The present work analyzes from the perception of disability, which means that it is an inability to be gifted in some areas, including the school environment. In this perspective, it analyses the operation of parent and disabled child relationship. Carters of the relationship between the level of education, the educational style of parents and school resilience in hearing impaired children, of Ivorian school of deaf. To this end, we were interested in 18 ivoirians children and their parents, 9 girls and 9 boys aged 10 to 12years, from disadvantaged social background. From the scale of parental educational styles of Terrisse and Larose (2000), the inventory forms of resilience of Békaert, Masclet and Caron (2011) and the Rorschach test (1921), we observed the different educational styles and types of resilient behavior. Overall, the results obtained show that, the educational level and educational style parents, influence the different forms of academic resilience, in hearing deficient children. However, this work could not demonstrate the relationship of the level of secondary school and academic resilience challenge type. The results validate the whole analysis of certain theoretical constructs and the facts noted by other studies, according to which, parents play a role in the autonomy and self-determination of disabled children.